RELATIONSHIP BETWEEN TRAUMA HISTORY AND FAMILY ENVIRONMENT WITH SYMPTOMS OF MENTAL EMOTIONAL DISORDERS IN STUDENTS IN MA NURUL HUDA WORKING AREA OF PUSKESMAS KRAGAN 1 - Chandiq, Noor; Hartinah, Dewi; Cahyani, Emi Catur (Jurnal Ilmu Keperawatan dan Kebidanan, 2025)
In carrying out their developmental tasks, adolescents will also experience several conflicts which have an impact on the emergence of feelings of insecurity, anxiety, and depression. The results of a preliminary study conducted by researchers on 10 students of MA Nurul Huda Kragan showed that 6 students experienced problems such as feeling anxious often. 2 students had difficulty sleeping. Of the 10 students who experienced painful experiences as many as 4 students and a bad family environment as many as 3 people. Purpose: to determine the relationship between trauma history and family environment with symptoms of mental emotional disorders in students in a private school Kragan Public Health Center 1. Methods this study uses a type of correlation with the first approach the researchers used a cross sectional approach. Sampling in this study by Sampling in this study using Total Sampling technique as many as 180. Data analysis using the Spearman Rank test. Results  there is a relationship between the family environment and the symptoms of mental emotional disorders in students in a private school in the Kragan 1 Public Health Center with a strong relationship direction ρ is 0.000 or a probability below 0.05. There is a relationship between a history of trauma and symptoms of mental-emotional disorders among students in a private school in the Kragan 1 Public Health Center with a moderate direction of relationship ρ is 0.000 or a probability below 0.05